Pengungkapan Korporasi dan Keterkaitannya dengan Informasi Lingkungan (Environmental Disclossure): Survei pada Perusahaan Publik di Bursa Efek Indoensia (BEI) tahun 2000 - Bambang Sudaryono (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2008)
The research based on random data from 68 listed company in Jakarta StockExchange in 2000. There are 25 company reported information about environment and the others did not report enviornment disclossure. The objective of the research is to know how listed company in JSX reported voluntary disclossure and how did listed company report mandatory enviornmental disclosssure. The research used univariat test for comparig mandatory disclossure and voluntary disclossure used by listed company in Jakarta Stock Exchange. The result of the research is the listed company reported voluntary enviromental disclossure more informatif than listed company reported mandatory environmental diclossure in financial statements. The other results of the result is more complete items reported in mandatory disclossure more informatif environmental data reported by listed company.